2007
DOI: 10.1089/ars.2007.1511
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Apoptosis in Neurodegeneration

Abstract: Apoptosis mediates the precise and programmed natural death of neurons and is a physiologically important process in neurogenesis during maturation of the central nervous system. However, premature apoptosis and/or an aberration in apoptosis regulation is implicated in the pathogenesis of neurodegeneration, a multifaceted process that leads to various chronic disease states, such as Alzheimer's (AD), Parkinson's (PD), Huntington's (HD) diseases, amyotrophic lateral sclerosis (ALS), spinal muscular atrophy (SMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
128
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(136 citation statements)
references
References 406 publications
2
128
0
1
Order By: Relevance
“…Apoptosis has been demonstrated to have a crucial role in SMA motor neuron degeneration. 47,48 A difference in methylation level was found for a CpG site related to the CYTSB gene (sperm antigen with calponin homology and coiled-coil domains 1). NSP5a3b and NSP5b3b protein isoforms encoded by CYTSB are predicted to have a CH (Calponin-like) domain, which is similar to the CH domain of actin-binding proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis has been demonstrated to have a crucial role in SMA motor neuron degeneration. 47,48 A difference in methylation level was found for a CpG site related to the CYTSB gene (sperm antigen with calponin homology and coiled-coil domains 1). NSP5a3b and NSP5b3b protein isoforms encoded by CYTSB are predicted to have a CH (Calponin-like) domain, which is similar to the CH domain of actin-binding proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress represents a significant mechanism for the destruction of cells that can involve apoptotic cell injury. Apoptotic induced oxidative stress in conjunction with processes of mitochondrial dysfunction can contribute to a variety of disease states such as diabetes, ischemia, general cognitive loss, Alzheimer's disease, and trauma [47][48][49]. As an early event in the dynamics of cellular apoptosis, membrane PS externalization can become a signal for the phagocytosis of cells.…”
Section: Oxidative Stress Apoptosis and Epomentioning
confidence: 99%
“…It has recently been shown that genes involved in the apoptotic process are replicated early during processes that involve cell replication and transcription, suggesting a much broader role for these genes than originally anticipated (Cohen, et al, 2007). Apoptotic induced oxidative stress in conjunction with processes of mitochondrial dysfunction can contribute to a variety of disease states such as diabetes, ischemia, general cognitive loss, Alzheimer's disease, and trauma (Chong, et al, 2005e, Chong, et al, 2005f, Harris, et al, 2007, Leuner, et al, 2007, Okouchi, et al, 2007. Oxidative stress can lead to apoptosis in a variety of cell types that involve neurons, endothelial cells (ECs), cardiomyocytes, and smooth muscle cells through multiple cellular pathways , Harris, et al, 2007, Karunakaran, et al, 2007, Verdaguer, et al, 2007.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Caspases are composed of three domains including an N-terminal prodomain, a large subunit, and a small subunit (Earnshaw, et al, 1999). As a result of their activation sequence, caspases are classified as either initiator caspases (also known as apical caspases) or effector caspases , Okouchi, et al, 2007. An initiator caspase cleaves and subsequently activates an effector caspase.…”
mentioning
confidence: 99%